Where the Ecological Gaps Remain, a Modelers' Perspective - Fulton, Elizabeth A.; Blanchard, Julia L.; Melbourne-Thomas, Jessica; Plagányi, Éva E.; Tulloch, Vivitskaia J. D. (Frontiers in Ecology and Evolution, 2019)
Humans have observed the natural world and how people interact with it for millennia. Over the past century, synthesis and expansion of that understanding has occurred under the banner of the ‘new’ discipline of ecology. The mechanisms considered operate in and between many different scales – from the individual and short time frames, up through populations, communities, land/seascapes and ecosystems. Whereas some of these scales have been more readily studied than others – particularly the population to regional landscape scales – over the course of the past twenty years new unifying insights have been possible via the application of ideas from new perspectives, such as the fields of complexity and network theory. At any sufficiently large gathering (and with sufficient lubrication) discussions over whether ecologists will ever uncover unifying laws and what they may look like still persist. Any pessimism expressed tends to grow from acknowledgement that gaping holes still exist in our understanding of the natural world and its functioning, especially at the smallest and grandest scales. Conceptualisation of some fundamental ideas, such as evolution, are also undergoing review as global change presents levels of directional pressure on ecosystems not previously seen in recorded history. New sensor and monitoring technologies are opening up new data streams at volumes that can seem overwhelming but also provide an opportunity for a profusion of new discoveries by marrying data across scales in volumes hitherto infeasible. As with so many aspects of science and life, now is an exciting time to be an ecologist.